Rational Interpretation of Numerical Quantity in Argumentative Contexts - Cummins, Chris; Franke, Michael (Frontiers in Communication, 2021)
Numerical descriptions furnish us with an apparently precise and objective way of summarising complex datasets. In practice, the issue is less clear-cut, partly because the use of numerical expressions in natural language invites inferences that go beyond their mathematical meaning, and consequently quantitative descriptions can be true but misleading. This raises important practical questions for the hearer: how should they interpret a quantitative description that is being used to further a particular argumentative agenda, and to what extent should they treat it as a good argument for a particular conclusion? In this paper, we discuss this issue with reference to notions of argumentative strength, and consider the strategy that a rational hearer should adopt in interpreting quantitative information that is being used argumentatively by the speaker. We exemplify this with reference to UK universities’ reporting of their REF 2014 evaluations. We argue that this reporting is typical of argumentative discourse involving quantitative information in two important respects. Firstly, a hearer must take into account the speaker’s agenda in order not to be misled by the information provided; but secondly, the speaker’s choice of utterance is typically suboptimal in its argumentative strength, and this creates a considerable challenge for accurate interpretation.